1992
DOI: 10.1111/j.1755-3768.1992.tb04879.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term effects of proparacaine on human corneal thickness

Abstract: 0.5% proparacaine HCl is commonly used for topical anaesthesia in ultrasound pachometry prior to refractive surgery. This drug is known to alter corneal epithelial adhesion. Does 0.5% proparacaine result in an alteration in corneal thickness due to changes in the corneal epithelium? Corneal thickness was measured by optical pachometry at 30 sec intervals for 15 min under 3 experimental conditions; 1) 2 drops of artificial tears, 2) 1 drop of 0.5% proparacaine, 3) 2 drops of 0.5% proparacaine. Baseline measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 4 publications
(3 reference statements)
2
29
1
4
Order By: Relevance
“…The underlying cause of the measurement bias is not clear, although possibilities include corneal compression, which is inherent in the confocal technique and may induce measurement error, as well as epithelial edema from topical anesthetic use. 1 Our findings are consistent with a previous study 2 comparing in vivo confocal microscopy with specular microscopy that found confocal microscopy to slightly overestimate corneal thickness. In contrast, a study 3 of a clinical tandem scanning confocal microscope found measurements to be slightly lower than those recorded by ultrasonic pachymetry.…”
Section: Discussionsupporting
confidence: 83%
“…The underlying cause of the measurement bias is not clear, although possibilities include corneal compression, which is inherent in the confocal technique and may induce measurement error, as well as epithelial edema from topical anesthetic use. 1 Our findings are consistent with a previous study 2 comparing in vivo confocal microscopy with specular microscopy that found confocal microscopy to slightly overestimate corneal thickness. In contrast, a study 3 of a clinical tandem scanning confocal microscope found measurements to be slightly lower than those recorded by ultrasonic pachymetry.…”
Section: Discussionsupporting
confidence: 83%
“…Herse y Siu (2), observaron que una gota de propacaina 0,5% provocaba un ligero aumento de ECC que se recuperaba en dos minutos, efecto que se hacía estadís-ticamente significativo cuando se instilaban dos gotas de dicho anestésco (incremento de aproximadamente 15 micras). Estos autores atribuyeron dicho incremento, que tardaba de 8 a 10 minutos en recuperarse, a un edema transitorio del estroma corneal (2). Alemán y col (3) estudiaron, también mediante Orbscan, los cambios en el espesor corneal después de aplicar tetracaína 0,5%, y observaron un aumento del espesor corneal de 9,4 micras, ligeramente mayor al encontrado por Herse y Siu (2) al instilar una gota de propacaina.…”
Section: Discussionunclassified
“…Estudios previos sobre el efecto de diferentes anestésicos tópicos en el espesor de la córnea, llevados a cabo con diferentes métodos paquimétricos, se centraban en el espesor corneal central (ECC), existiendo diferencias en sus resultados; mientras que en algunos casos se observa un incremento transitorio de espesor, otros no encuentran variaciones significativas del ECC (2)(3)(4)(5). En cuanto a las variaciones de espesor paracentral inducidas por anestesia tópica, Asensio y col (6), utilizando el Orbscan, observan que no existen variaciones significativas en el espesor corneal a los 3 minutos de la instilación de oxibuprocaina al 0,4%.…”
Section: Introductionunclassified
“…The instillation of one drop of proparacaine 0.5% is capable of increasing, though transient, corneal thickness (Herse and Siu, 1992;Nam et al, 2006), thus a greater reading of IOP is expected.…”
Section: Discussionmentioning
confidence: 99%